Laser-Induced MXene-Functionalized Graphene Nanoarchitectonics-Based Microsupercapacitor for Health Monitoring Application - Deshmukh, Sujit; Ghosh, Kalyan; Pykal, Martin; Otyepka, Michal; Pumera, Martin (ACS nano, 2023)
Microsupercapacitors (micro-SCs) with mechanical flexibility have the potential to complement or even replace microbatteries in the portable electronics sector, particularly for portable biomonitoring devices. The real-time biomonitoring of the human body's physical status using lightweight, flexible, and wearable micro-SCs is important to consider, but the main limitation is, however, the low energy density of micro-SCs as compared to microbatteries. Here using a temporally and spatially controlled picosecond pulsed laser, we developed high-energy-density micro-SCs integrated with a force sensing device to monitor a human body's radial artery pulses. The photochemically synthesized spherical laser-induced MXene (Ti3C2Tx)-derived oxide nanoparticles uniformly attached to laser-induced graphene (LIG) act as active electrode materials for micro-SCs. The molecular dynamics simulations and detailed spectroscopic analysis reveal the synergistic interfacial interaction mechanism of Ti-O-C covalent bonding between MXene and LIG. The incorporation of MXene nanosheets improves the graphene sheet alignment and ion transport while minimizing self-restacking. Furthermore, the micro-SCs based on a nano-MXene-LIG hybrid demonstrate high mechanical flexibility, durability, ultrahigh energy density (21.16 × 10-3 mWh cm-2), and excellent capacitance (∼100 mF cm-2 @ 10 mV s-1) with long cycle life (91% retention after 10 000 cycles). Such a single-step roll-to-roll highly reproducible manufacturing technique using a picosecond pulsed laser to induce MXene-derived spherical oxide nanoparticles (size of quantum dots) attached uniformly to laser-induced graphene for biomedical device fabrication is expected to find a wide range of applications.
Keywords: covalent bonding; oxidy; arterie; Laser-induced MXene; grafit; Humans; Arteries; Oxides; lidé; lasery; biomonitoring device; microsupercapacitor; Lasers; Graphite; laser-induced graphene